ChemInform Abstract: A Decade of Dinuclear Technetium Complexes with Multiple Metal—Metal Bonds. Issue 44 (4th November 2014) - Poineau, Frederic; Forster, Paul M.; Todorova, Tanya K.; Johnstone, Erik V.; Kerlin, William M.; Gagliardi, Laura; Czerwinski, Kenneth R.; Sattelberger, Alfred P.
Abstract Review: [preparation, solid state and electronic structures, and spectroscopic properties of (Bu4N)2Tc2X8, Tc2(OAc)4X2, Tc2(OAc)2Cl4, cesium salts of Tc2X83‐, and Tc2X4(PMe3)4 (X: Cl, Br); 38 refs.